A Randomised Clinical Trial to Compare the Post Dural Puncture Headache Following Spinal Anaesthesia using 27 G Quincke’s and 27 G Whitacre’s Spinal Needles - and Shivanand Karigar1, S. N. Suresh1,2* (Recent Research in Science and Technology, 2010)
Abstract Background and objectives Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Spinal anaesthesia is one of the most commonly used techniques in anaesthesia.Â It is economical, safe, cost effective, easy, needs less sophisticated anaesthetic equipment, drugs, post operative care hence preferred over general anaesthesia and most popular because of its profound analgesia and muscle relaxation. Objectives of the present study were to know the incidence of post dural puncture headache (PDPH), number of attempts for successful sub arachnoid block and incidence of failed spinal anaesthesia by using 27 G Quinckeâ€™s and Whitacreâ€™s spinal needles. Methodology This one year randomized clinical trial was conducted in the Department of Anaesthesiology, at our hospital during the period of January 2009 to December 2009 on 352 patients between 20 to 60 years of age with ASA grade I and II undergoing lower abdominal and lower limb surgeries during the study period. The Institutional Ethical Clearance and written informed consent from patients was obtained the incidence of PDPH, number attempts and failed spinal anaesthesia were assessed. Results In this study female preponderance was seen. Significantly high incidence of PDPH was recorded in Quincke group (3.98%) as compared to 0.57% in Whitacre group (p=0.031). Significantly less number of attempts were required using Whitacre 27 G needle (p=0.0001). Failed rates were higher in patients using Whitacre 27 G needle as compared Quincke 27 G needle (3.98% versus 2.84%). Interpretation and conclusion Overall the Whitacre 27 G needle has better results with respect to PDPH and number of attempts required for successful subarachnoid block whereas the incidence of failed spinal anaesthesia was less with Quincke 27 G needle. Keywords: Post dural puncture headache; Failed spinal anaesthesia; Sub-arachnoid block; Quincke needle; Whitacre needle <span style="line-height: 200%; font-family: ";Arial Narrow";,";sans-serif";; letter-spacing: -0.3pt; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: EN-SG; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-SG; mso-bidi-language: AR-SA;" lang="EN-SG">